Estrategias metodológicas para mejorar la ortografía de los niños de 10mo año de la Unidad Educativa Juan E. Verdesoto - Vega Rojas, Lisbeth Jarued (2023)
The methodological strategies used in this research emphasize informing elementary school teachers who teach subjects related to the alphabet codes, especially the correct use of spelling. This research seeks to improve the strategies that are being used in the Juan E. Verdesoto educational unit, which was carried out based on the objective that was set, which is to propose methodological strategies to improve the spelling of 10-month-old students. The case study research was carried out by means of a mixed research consisting of qualitative and quantitative approaches, in addition to techniques such as observation, survey and evaluation of oral and written spelling comprehension. For the measurement of the sample we worked with a group of 19 students who were evaluated and the 6 teachers were surveyed, all based on the dimensions that had each of the independent variables methodological strategies and dependent spelling. In the first dimensions we investigated: level of difficulty in understanding texts, time dedicated to carry out new planning, team work, use of dynamic resources; in the other dimension: resources to modify errors, reading comprehension, additional tutoring, identification and comprehension of reading, improvement of methodological strategies.